Post-transcriptional regulation by HuR in colorectal cancer: impacts on tumor progression and therapeutic strategies - Shi, Yilin; Zhou, Zhen; Liu, Cong; Liu, Jing; Xie, Mengying; Chen, Xin; Dixon, Dan A.; Wu, Xiaoqing; Yang, Lingling (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is the third most common malignancy worldwide and the second leading cause of cancer-related deaths. Its progression is driven by genetic and epigenetic alterations, with increasing evidence emphasizing the role of the transcriptome, particularly post-transcriptional modifications. Human antigen R (HuR), an RNA-binding protein (RBP), plays a crucial role in post-transcriptional regulation of gene expression. In the context of tumor progression, HuR affects a range of cellular processes, including cell proliferation, survival, and metabolic reprogramming, via regulating target mRNA stability and translation. Additionally, HuR influences the tumor microenvironment (TME) through modulating target mRNAs involved in inflammation, immune responses, extracellular matrix remodeling and angiogenesis. Despite these insights, the precise mechanisms by which HuR regulates post-transcriptional process in CRC remain unclear. This review first provides an overview of HuR’s roles and the underlying mechanisms involved in CRC progression, including its regulation of mRNA expression, control of the cell cycle, and modulation of the TME. We also discussed the potential of HuR as a therapeutic target, exploring how targeting HuR could slow down CRC progression and metastasis, ultimately leading to more effective and personalized treatment strategies.